Pleistocene Involutions and Patterned Ground in France: Examples and Analysis Using a GIS Database. (5th September 2017) - Bertran, Pascal; Andrieux, Eric; Antoine, Pierre; Deschodt, Laurent; Font, Marianne; Sicilia, Deborah
Abstract: A georeferenced database is used to analyse the distribution of Quaternary soft‐sediment deformation structures across France. They include features visible in aerial photographs (soil stripes and cells) and features described in cross‐section (involutions). Overall, there is no clear relation between the distribution of features and the locations of known faults and earthquakes in available databases. In contrast, the distribution agrees with that of Pleistocene periglacial structures. Most of the soil stripes and cells are located north of 47.5°N, i.e. in the zone of ice‐wedge pseudomorphs, and can be interpreted as deformation structures of an active layer in permafrost terrain. The height of the involutions is influenced by the nature of the filling, the substrate and latitude. Deformation structures are larger in coarse material, reflecting the role of drainage and thermal conductivity. Their height increases northward to ca. 2 m at 48°N. This is thought to reflect the increase in thickness of the layer subjected to freeze–thaw cycles. Bowl‐shaped structures separated by coarse pillars, which correspond to soil stripes seen in section, have formed on slopes in settings unfavourable to the generation of high pore‐water pressure. Their genesis is probably related to differential frost heave. Ball‐and‐pillow structures and diapirs are common in flat and poorly drained terrain, and formed by liquefaction and sometimes fluidisation in a periglacial setting. Copyright © 2017 John Wiley & Sons, Ltd.